Diseño de un sistema de gestión de calidad basado en la norma ISO 9001:2015 para la Empresa Agrosistemas S.A. - Solórzano Figueroa, María Fernanda (2019)
The present research project took place in the company AGROSISTEMAS S.A., taking into acount that its main objective is the design of a quality management system based on the ISO 9001:2015 standard for the company AGROSISTEMAS S.A., with the purpose of optimizing the quality management that makes up the processes and activities in that company. The survey was taken as a reference to the personnel working in the company, to be aware that if the company contains the ISO 9001: 2015 standard within its standard parameters of quality in the product, realizing that the company does not have the standard in carrying out their activities, although the company's staff was able to state that they had heard about the standard, they have a notion that the norm exists, but they do not dominate the necessary knowledge of how the ISO 9001: 2015 standard is treated. The procedures that were carried out in this investigation towards the company AGROSISTEMAS S.A., is a discernment of the study carried out for the planning, of a Quality Management system based on the ISO 9001: 2015 standard, for the processes and activities of the company before mentioned. With the help of the results obtained in the invstigation, it can be noticed that the company needs a quality system, based on the ISO 9001: 2015 standard, since they measure their quality by observing the material they use in the preparation of their agricultural products and the termination of such products, as all work done in perfect conditions without any failure is mechanical or physical so the customer is also aware of the details of the finish. Keywords: ISO, Quality, Standard, 9001, Design, Planning